Adventure Game Show:Audience Involvement, Destination Image and Audience Behavior - Irwansyah Irwansyah; Dwininta Widyastuti (IAES Indonesia Section, 2018)
Currently the popularity of the show television programs is on the rise. This entertainment program attracts viewers' attention because it is dominated by games and usually involves the physical activity of the participants of the game show competition. The location of the shooting event also varied, including adventure-themed tourism destinations involving natural beauty. This study uses an experimental study to measure the behavior intentions of game show viewers of adventure tours that aired in the program. This study proves that the relationship of audience involvement and behavioral intentions to travel to tourist destinations is mediated by cognitive and affective imagery. In particular, cognitive imagery can be significantly effects affective imagery, and both cause with behavioral intentions. Television media deals with psychological process travel, so it is found that audience involvement leads to audience behavior intentions. Meanwhile, the image of a tourist destination mediates this relationship, the image that gives the perception of the cognitive image and the affective image, so that these two variables are found to be important mediators. Therefore, the management of television programs as media messengers need to focus on creating more positive picture of adventure-themed tourism destinations, which will lead to the formation of positive affective image also to the location. The higher the image of the tourist destination for the viewers will lead to higher travel intentions in the future.